Factors influencing adherence and employee perceptions towards safety control in a mining company - Modiba, Thami Malcolm (My University, 2018)
The majority of mine health and safety authorities around the world agree that the quality of safety standards is of increasing importance to the mining industry across the world (Kleyn & du Plessis 2016:309). Mining companies in many countries such as New Zealand, (an island country in the south-western Pacific Ocean), Australia, South Africa and China have taken up the challenges of guaranteeing liability and improving performance of the safety and health of their workers, aware that many workers are injured, if not fatally. These incidents result in production loss. This study provides not only an opportunity to evaluate the status of the safety control measures of the work system in a mining company, but also enables management to pinpoint the causes of poor safety performance and implement efforts that ensure safety improvement. The primary objectives of this study were to examine factors influencing the adherence and employee perceptions towards safety control measures in a mining company. Furthermore, the governments in many countries have tried to implement legislation to try to curb the scourge of industrial accidents. Safety disclosures of the annual reports from the Department of Mineral Resources (DMR) of South African mining organisations, discloses 10 major mining accidents that happened in 2015 at Northern Cape mining companies. Six of these accidents occurring from a small mining sector and four from a large mining sector, except previous year’s safety records as detailed in this study. A quantitative approach was adopted for the study. The data were collected using a sample of 200 participants in which a survey questionnaire was administered to permanent mine employees and full time contractors in the mine. A simple sampling technique was used and data were then analysed using the Statistical Package for the Social Science (SPSS) version 25.0 to formulate frequency tables and descriptive analysis graphs. Furthermore, one-way analysis of variance (ANOVA) and t-test were utilised to analyse the data and examine significant differences between employee perceptions and attitudes towards safety control measures, age and length of service (Willemse 2009:118-121). The results reveal that although the mine was considered compliant, with its employees showing a positive attitude towards safety control measures, ANOVA revealed different perceptions of employees based on their age and years of experience. However, no differences were found in relation to gender and occupation. Based on the findings, this study further recommends future studies to be conducted in order to explore the effectiveness of implementing an internal system of self-evaluation as a starting point in any safety improvement process. An effective system of internal self-evaluation will trademark the mining sector internationally and improve workers’ safety by improving effectiveness and assurance of the control measures and the level of control performance criteria. The system should create the awareness of adherence to safety control measures and deal with employee perception towards safety adherence in mining. In addition it should be a system that ensures a structured and standardised approach to learning from incidents and that all necessary steps are followed to safeguard against repeats of incidents and accidents through an effective incident investigation process (Van den Berg 2014:11). The findings of the study revealed that the leadership in the mine has a strong, positive and significant influence on the performance of safety. In this regard, this study recommends that an effective employee engagement system to be developed and that mine managers establish a safety control charter that must be understood by the mine workers, develop a code of ethics that requires ethical and honest behaviour from all employees in order to improve safety performance and learn from these accomplishments. Mine workers will take their cue from the attitude and example displayed by management, therefore, it is recommended that mine management develop an organisational culture, which assigns authority and responsibility to employees and organises and develops employees with direction provided by management that determines the type of culture in that mine. To minimise or reduce the risk of health exposure of each activity as highlighted under Regulation 9 of the Mine Health and Safety Act (29 of 1996), it is recommended that mine manager’s enforce the use of protective equipment. The leadership and human resources, mine workers and all persons who may be affected by the mining activities in the surrounding area of operation need to be aware of the factors that can impact their well-being. The study also presented managers, mine owner and other decision makers within the mining company with important insight on key areas of factors that may require particular attention in order to enhance their operational strategies towards zero harm in the mine.
M.Tech. (Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: adherence, culture, employees’ perceptions, fatality, legal-framework, mining, safety controls measures; Employees -- Attitudes.; Industrial safety -- South Africa.; Mining corporations -- Safety measures -- South Africa.